Core binding factor acute myeloid leukemia: the impact of age, leukocyte count, molecular findings, and minimal residual disease. (25th July 2013) - Hoyos, Montserrat; Nomdedeu, Josep F.; Esteve, Jordi; Duarte, Rafael; Ribera, Josep M.; Llorente, Andreu; Escoda, Lourdes; Bueno, Javier; Tormo, Mar; Gallardo, David; de, Maria Paz Queipo; Martí, Josep M.; et al.
Abstract Purpose Most patients with acute myeloid leukemia (AML) and genetic rearrangements involving the core binding factor (CBF) have favorable prognosis. In contrast, a minority of them still have a high risk of leukemia recurrence. This study investigated the adverse features of CBF AML that could justify investigational therapeutic approaches. Patients and methods One hundred and fifty patients (median age 42 yr, range 16–69) with CBF AML (RUNX1‐RUNX1T1 n = 74; CBFB‐MYH11 n = 76) were prospectively enrolled into two consecutive CETLAM protocols at 19 Spanish institutions. Main clinic and biologic parameters were analyzed in the whole series. In non‐selected cases with available DNA samples, the impact of molecular characterization and minimal residual disease (MRD) was also studied. Results Overall, complete remission (CR) rate was 89% (94% in ≤50 yr old and 72% in >50 yr, P = 0.002). At 5 yr, cumulative incidence of relapse (CIR) was 26 ± 1%, disease‐free survival (DFS) 62 ± 6%, and overall survival (OS) 66 ± 4%. In multivariate analyses, leukocyte count above 20 × 109/L, BAALC over‐expression, and high copy numbers of RUNX1‐RUNXT1 or CBFB‐MYH11 after induction chemotherapy (CT) led to increased relapse rate. Regarding OS, age >50 yr, leukocyte count above 20 × 109/L, and increased MN1 expression were adverse features. Conclusion Age, leukocyte counts, BAALC, and MN1 gene expressions as well as high copy numbers of RUNX1‐RUNXT1 or CBFB‐MYH11 after induction chemotherapy are useful tools to predict the outcome and should be considered for risk‐adapted therapy.